Coping with summer weather: management strategies to control heat stress - Smith, John F., 1962-; Harner, Joseph P. (Kansas Agricultural Experiment Station, 2011)
Heat stress occurs when a dairy cow’s heat load is greater than her capacity to lose heat. The effects of heat stress include: increased respiration rate, increased water intake, increased sweating, decreased dry matter intake, slower rate of feed passage, decreased blood flow to internal organs, decreased milk production, and poor reproductive performance. The lower milk production, and reproductive performance cause economic losses to commercial dairy producers. This review will discuss methods that can be used on commercial dairy farms to reduce the effects of heat stress on dairy cattle.
Keywords: Heat stress; Summer; Cooling